Fcγ receptor-dependent antibody effector functions are required for vaccine protection against infection by antigenic variants of SARS-CoV-2 - Mackin, Samantha R; Desai, Pritesh; Whitener, Bradley M; Karl, Courtney E; Liu, Meizi; Baric, Ralph S; Edwards, Darin K; Chicz, Taras M; McNamara, Ryan P; Alter, Galit; Diamond, Michael S (bioRxiv, 2022)
Emerging SARS-CoV-2 variants with antigenic changes in the spike protein are neutralized less efficiently by serum antibodies elicited by legacy vaccines against the ancestral Wuhan-1 virus. Nonetheless, these vaccines, including mRNA-1273 and BNT162b2, retained their ability to protect against severe disease and death, suggesting that other aspects of immunity control infection in the lung. Although vaccine-elicited antibodies can bind Fc gamma receptors (FcγRs) and mediate effector functions against SARS-CoV-2 variants, and this property correlates with improved clinical COVID-19 outcome, a causal relationship between Fc effector functions and vaccine-mediated protection against infection has not been established. Here, using passive and active immunization approaches in wild-type and Fc-gamma receptor (FcγR) KO mice, we determined the requirement for Fc effector functions to protect against SARS-CoV-2 infection. The antiviral activity of passively transferred immune serum was lost against multiple SARS-CoV-2 strains in mice lacking expression of activating FcγRs, especially murine FcγR III (CD16), or depleted of alveolar macrophages. After immunization with the preclinical mRNA-1273 vaccine, protection against Omicron BA.5 infection in the respiratory tract also was lost in mice lacking FcγR III. Our passive and active immunization studies in mice suggest that Fc-FcγR engagement and alveolar macrophages are required for vaccine-induced antibody-mediated protection against infection by antigenically changed SARS-CoV-2 variants, including Omicron strains.